Systematic review—pancreatic involvement in inflammatory bowel disease. Issue 12 (3rd May 2022) - Massironi, Sara; Fanetti, Ilaria; Viganò, Chiara; Pirola, Lorena; Fichera, Maria; Cristoferi, Laura; Capurso, Gabriele; Invernizzi, Pietro; Danese, Silvio
Summary: Background: Inflammatory bowel disease (IBD) is a chronic inflammatory immune‐mediated disorder of the gut with frequent extra‐intestinal complications. Pancreatic involvement in IBD is not uncommon and comprises a heterogeneous group of conditions, including acute pancreatitis (AP), chronic pancreatitis (CP), autoimmune pancreatitis (AIP) and pancreatic exocrine insufficiency (PEI); however, data on such an association remain sparse and heterogeneous. Method: PubMed/MEDLINE and EMBASE databases were searched for studies investigating pancreatic involvement in patients with IBD. Results: Four thousand one hundred and twenty‐one records were identified and 547 screened; finally, 124 studies were included in the review. AP is the most frequent pancreatic manifestation in IBD; the majority of AP cases in IBD are due to gallstones and drugs but cases of idiopathic AP are increasingly reported. AIP is a rare disease, but a strong association with IBD has been demonstrated, especially for type 2 and ulcerative colitis. The pathogenetic link between IBD and AIP remains unclear, but an immune‐mediated pathway seems plausible. An association between CP and PEI with IBD has also been suggested, but data are to date scarce and conflicting. Conclusion: This is the first systematic review of the association between IBD and pancreatic diseases. Gallstones and drugs should be considered the most probable causes of AP in IBD, with type 2 AIP also being possible. Abstract : Systematic review. Pancreatic involvement in inflammatory bowel disease (IBD). The wide spectrum of pancreatic involvement in patients with IBD may represent a challenge. From the 124 studies analyzed, acute pancreatitis (AP) is the most frequent pancreatic manifestation in IBD; the majority of AP cases in IBD are due to gallstones and drugs, but cases of idiopathic AP are increasingly reported. Autoimmune pancreatisis is a rare disease, but a strong association with IBD has been demonstrated, especially for type 2 and ulcerative colitis.